Study on watermarking scheme using threshold value and S-Box. (1st January 2014) - Kang, Jungho; Kim, Sungsoo; Jun, Moonseog
Digital data can be easily copied and distributed, and since the original is exactly the same as the copy, the author would be unable to distinguish between the two. This is currently becoming a serious problem, resulting in a spear-and-shield like confrontation between those who are trying to stop illegal replication and those who are trying to access illegal copies. Digital watermarking is attracting attention as a means of providing copyright protection and authentication for multimedia content facing such difficulties. A digital watermark inserts information into multimedia content without the users' knowledge, and in the event of a copyright issue, the information can be extracted, providing the author with the rightful claim of ownership. In this thesis, a watermark is not only inserted in the LSB bit like the thesis of Ping Wah Wong and Nasir Memon, but the insertion position of the watermark is randomly chosen using a threshold value and S-Box to prevent an attacker from obtaining or manipulating the inserted information. In addition, threshold values that result in a minimum amount of image deterioration due to variable insertion were evaluated experimentally.